Young Hunters of the Lake; or, Out with Rod and Gun - Stratemeyer, Edward, 1862-1930 (Salt Lake City, UT : Project Gutenberg, 2004)
"Young Hunters of the Lake; or, Out with Rod and Gun" by Captain Ralph Bonehill is an adventure novel written in the early 20th century. The narrative follows a group of four boys who embark on summer camping and hunting trips, brimming with excitement and the spirit of outdoor exploration. The protagonists, Snap, Shep, Whopper, and Giant, are eager to delve into the wilderness, facing off against rivals while navigating the various escapades that come their way, including dealing with a ghost story and mischief from local boys. The opening of the book introduces the characters as they discuss plans for swimming at Lane's Cove and reminisce about their previous adventures. It highlights the budding camaraderie and playful banter among the boys, showcasing their personalities through their dialogue. Not long after, they face a humorous incident with a ram while on their outing, setting a light-hearted tone. The narrative outlines their intentions to embark on another thrilling camping trip, which promises challenges and the allure of the wild, suggesting that the journey ahead will be filled with both youthful mischief and moments of suspense. (This is an automatically generated summary.)
Release date is 2004-07-19
Keywords: Fishing -- Juvenile fiction; Hunting -- Juvenile fiction